Competition, Innovation and Productivity Growth A Review of Theory and Evidence - Ahn, Sanghoon (OECD Economics Department Working Papers, 2002)
This paper reviews recent studies on the links between competition, innovation and productivity growth in the long run. From a long-run perspective, one can see that gains from competition-enhancing regulatory reform are likely to exceed static gains observed in the short run since firms will continue to innovate in ways they would not have under regulation. By taking a dynamic perspective on competition and efficiency, one can also understand better the new modes of competition observed in "dynamically competitive" industries. This paper also attempts to cover some of relatively new research areas including: i) measuring welfare gains from product innovation; ii) competition and efficiency in e-commerce, education, and health care; and iii) interactions between product- and factor-market competition ...